SIMBIOSIS BUDAYA DAN GERAK: ANALISIS HUBUNGAN ANTARA OLAHRAGA PENCAK SILAT DAN NILAI-NILAI KEBUDAYAAN SUNDA - Nadil Ulum Annafis; Amrul Hayat; Ibnu Sina; Syahriel Fajri; Erpin Erpin; Nasrul Nasrul; Ahdi Muhyi; M. Dzakwan Alamsyah; Muhamad Nur Faqih (CV. Denasya Smart Publisher, 2025)
In the era of globalization that threatens the sustainability of local culture, pencak silat as a traditional Sundanese martial art has a strategic urgency in maintaining the cultural identity of the community. This study aims to analyze the reciprocal relationship between pencak silat and Sundanese culture, as well as to reveal the cultural values ​​reflected in the movements and rituals of pencak silat. Using a descriptive qualitative approach with ethnographic methods, the study was conducted at traditional silat schools in Garut and Tasikmalaya through participatory observation, in-depth interviews, and documentation studies. The results of the study indicate that pencak silat not only functions as a sport, but also as a symbolic system that represents values ​​such as respect, patience, and spirituality, as well as a medium for cultural inheritance through narratives, music, and ceremonies. These findings strengthen the understanding of pencak silat as a complex and meaningful intangible cultural heritage. This study suggests the need for integration of pencak silat in local education and support for community-based cultural preservation policies. Further studies are recommended to expand the scope of the area and a multidisciplinary approach to enrich perspectives